The Essential Properties of Interest and Money - Lerner, Abba P. (Quarterly Journal of Economics, 1952)
I. Concepts, 172. — II. Measurements, 173. — III. Equilibrium, 176. — IV. Commentary, 180. — V. Conclusion, 188.